Analisis Kinerja Keuangan di Tinjau dari Rasio Likuiditas, Solvabilitas, dan Profitabilitas Pada PT Dhanu Sumber Tani - Firman Alimuddin; Arifuddin Arifuddin; Andi Alfianto Anugrah Ilahi (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The purpose of this study is to determine financial performance in terms of liquidity, solvency and profitability ratios. The data analysis method used in this research is quantitative descriptive by calculating the Current Ratio, Cash ratio, Debt To Assets Ratio, Debt to Equity Ratio, Return On Assets, and Return On Equity. The results of this study Current ratio in 2018-2020 is 1.22 times, 1.28 times, 1.48 times not according to industry standards. Cash ratio in 2018-2020 is 20%, 16%, 16% not according to industry standards. The 2018-2019 DAR is 31%, 32%, 31%, according to industry standards. DER 2018-2020 is 46%, 48%, 45% according to industry standards. ROA for 2018-2020 is 11%, 11%, 14% not according to industry standards. ROE for 2018-2020 is 16% 17% 20% not yet according to industry standards.